2018
DOI: 10.1097/01.aog.0000532919.12355.64
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Assessment of Blood Loss During Cesarean Delivery Improves Estimate of Postoperative Hemoglobin [17B]

Abstract: INTRODUCTION: The need for red blood cell transfusion for patients having cesarean delivery is ideally based on an evaluation of both clinical indicators and laboratory studies. In practice, transfusions are often given to women based on estimated intraoperative blood loss (EBL) and/or the postoperative hemoglobin level. Since visual estimation is known to be inaccurate, we postulated that a more accurate determination using a novel colorimetric device would be better correlated with postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study did not rely on sophisticated method(s) for EBL, but the method of estimation was unified in all cesareans. In women with high EBL, Rubenstein et al 10 found that using a novel colorimetric device was a more accurate predictor of post-operative hemoglobin. Other authors 11 did not support the view that EBL or quantitative assessment of blood loss (QBL) methods accurately reflect the actual blood loss during scheduled cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not rely on sophisticated method(s) for EBL, but the method of estimation was unified in all cesareans. In women with high EBL, Rubenstein et al 10 found that using a novel colorimetric device was a more accurate predictor of post-operative hemoglobin. Other authors 11 did not support the view that EBL or quantitative assessment of blood loss (QBL) methods accurately reflect the actual blood loss during scheduled cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…The application has already been tested in vitro (10,11) and is capable of measuring Hb with acceptable accuracy in blood samples with a wide range of Hb levels and dilutions (9,12). The application provides real-time information on blood loss and has the potential to improve the management of bleeding patients and hemotherapy (13)(14)(15)(16)(17). To our knowledge, there is no study that directly compares a colorimetric blood loss estimate to the existing clinical practice of visual and gravimetric blood loss estimation in a simulated scenario with known blood volumes as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…The recently reported use of artificial intelligence (AI) namely Triton too is not feasible in these settings. 5,6 The pragmatic methods of assessing postpartum bleeding are visual estimation of blood loss (EBL) and quantitative assessment of blood loss (QBL) which includes direct collection (volumetric) added to that measured by weighing (gravimetric). EBL still remains the most commonly employed method in clinical practice in spite of various reports of gross underestimation of the actual blood loss by virtue of it being a subjective assessment.…”
Section: Introductionmentioning
confidence: 99%